Social determinants of mid- to long-term disaster impacts on health: A systematic review. (June 2016) - Nomura, Shuhei; Parsons, Alexander J.Q.; Hirabayashi, Mayo; Kinoshita, Ryo; Liao, Yi; Hodgson, Susan
Abstract: Disasters cause a wide range of health impacts. Although there remains a need to understand and improve acute disaster management, a stronger understanding of how health is affected in the medium and longer term is also required to inform the design and delivery of measures to manage post-disaster health risks, and to guide actions taken before and during events which will also lead to reduction in health impact. Social determinants exert a powerful influence on different elements of risk, principally vulnerability, exposure and capacity, and thus, on people's health. As disaster health data and research has tended to focus on the short-term health impacts, no systematic assessment of the social determinants of the mid- to long-term health impacts of disasters has been identified. We assessed the chronic health impacts of disasters and explored the potential socioeconomic determinants of health impact through a systematic review. Our findings, based on 28 studies, highlighted that regardless of health outcomes and event types, the influence of disasters on chronic heath persists beyond the initial disaster period, affecting people's health for months to years. Using the World Health Organization's conceptual framework for the social determinants of health, we identified a total of 35 themes across the three conceptual domains (determinants related to the socioeconomic and political context, structural determinants, and intermediate determinants) as potentially influencing disaster impact. Investment to tackle modifiable underlying determinants could aid disaster risk management, improve medium and long-term health outcomes from disasters, and build community resilience.